2018
DOI: 10.1080/15374416.2017.1405352
|View full text |Cite
|
Sign up to set email alerts
|

Testing Syndromes of Psychopathology in Parent and Youth Ratings Across Societies

Abstract: As societies become increasingly diverse, mental health professionals need instruments for assessing emotional, behavioral, and social problems in terms of constructs that are supported within and across societies. Building on decades of research findings, multisample alignment confirmatory factor analyses tested an empirically based 8-syndrome model on parent ratings across 30 societies and youth self-ratings across 19 societies. The Child Behavior Checklist for Ages 6-18 and Youth Self-Report for Ages 11-18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
3
20
0
2
Order By: Relevance
“…Although evidence of its scalar invariance was modest, it is probably as strong as can be expected for such a complex model tested across so many societies. Our prior alignment CFA study of an eight‐syndrome model of child psychopathology yielded similar results . We found strong evidence for configural and metric invariance but modest evidence for scalar invariance in ratings by 61 703 parents in 30 societies using the Child Behavior Checklist for Ages 6‐18 (CBCL) and in ratings by 29 486 youths in 19 societies using the Youth Self Report (YSR)…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although evidence of its scalar invariance was modest, it is probably as strong as can be expected for such a complex model tested across so many societies. Our prior alignment CFA study of an eight‐syndrome model of child psychopathology yielded similar results . We found strong evidence for configural and metric invariance but modest evidence for scalar invariance in ratings by 61 703 parents in 30 societies using the Child Behavior Checklist for Ages 6‐18 (CBCL) and in ratings by 29 486 youths in 19 societies using the Youth Self Report (YSR)…”
Section: Discussionsupporting
confidence: 63%
“…Our prior alignment CFA study of an eight-syndrome model of child psychopathology yielded similar results. 45 We found strong evidence for configural and metric invariance but modest evidence for scalar invariance in ratings by 61 703 parents in 30 societies using the Child Behavior Checklist for Ages 6-18 (CBCL) 46 and in ratings by 29 486 youths in 19 societies using the Youth Self Report (YSR). 46 The present findings are consistent with evidence for the generalizability of the seven-syndrome model derived from collateral ratings of elder psychopathology on the OABCL across 11 societies.…”
Section: Tested Modelmentioning
confidence: 80%
“…In cross-cultural analyses, Rescorla et al (2007) found that parents’ ratings were similar across 31 societies including Germany, indicating the multicultural robustness of the CBCL. Furthermore, the configural invariance of the 8-syndrome structure of the CBCL was confirmed in large cross-cultural studies including Germany ( Ivanova et al, 2007 , 2019 ). In the present study, the raw scale scores of the eight syndrome scales and the Internalizing Problems and Externalizing Problems were used.…”
Section: Methodsmentioning
confidence: 68%
“…It is standard practice to dichotomize a variable when transformations do not effectively normalize the distribution so the variable was dichotomized (Tabachnick & Fidell, 2013). At T2, 32 participants endorsed NSI and a dichotomized version of the variable (0 = No NSI, 1 = NSI Endorsed) was used for analyses Previous research has dichotomized full and abbreviated scales of the YSR as this measure of behavioral problems has low item endorsement in a nonclinical population (Ivanova et al, ; Lexcen, Vincent, & Grisso, ; Undheim & Sund, ; Verhulst et al, ). Data were first analyzed using the full Social Problems scale, and similar results were obtained consistent with prior literature comparing continuous and dichotomized scales of the YSR (Korhonen et al, ).…”
Section: Methodsmentioning
confidence: 99%